2003
DOI: 10.1016/s0042-6822(02)00044-2
|View full text |Cite
|
Sign up to set email alerts
|

Prime-boost vaccination with plasmid DNA encoding caprine-arthritis encephalitis lentivirus env and viral SU suppresses challenge virus and development of arthritis

Abstract: This study evaluated the efficacy of prime-boost vaccination for immune control of caprine arthritis-encephalitis virus (CAEV), a macrophage tropic lentivirus that causes progressive arthritis in the natural host. Vaccination of Saanen goats with pUC-based plasmid DNA expressing CAEV env induces T helper type 1 (Th1) biased immune responses to vector-encoded surface envelope (SU), and the plasmid-primed Th1 response is expanded following boost with purified SU in Freund's incomplete adjuvant (SU-FIA) (J. C. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
0
19
1
Order By: Relevance
“…However, recent vaccination studies in goats and sheep have shown that env immunization can induce lower virus loads or disease [12] and [19]. Significant differences between these studies and the present work exist.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…However, recent vaccination studies in goats and sheep have shown that env immunization can induce lower virus loads or disease [12] and [19]. Significant differences between these studies and the present work exist.…”
Section: Discussioncontrasting
confidence: 66%
“…However, recently it has been shown that immunization of goats with recombinant gp135 glycoprotein of CAEV induces neutralizing antibodies [11], suggesting that protective effects may be possible. Indeed, the use of plasmid DNA vaccination or live viral vectors encoding CAEV env gene has demonstrated that reductions in virus load and disease can be achieved [12].…”
Section: Introductionmentioning
confidence: 99%
“…So far no one has been able to show whether T cells are protective against MVV infection (17,18). Similar vaccination attempts against the small-ruminant lentiviruses (MVV and CAEV) have been unsuccessful at producing sterile immunity (10,11,13,22,37,41,46,53) and often make the pathology seen after infection worse (37,41,53). Indeed, CD4…”
Section: Discussionmentioning
confidence: 99%
“…Another means of improving DNA vaccines is to combine them with inactivated virus or purified protein in a DNA prime-protein boost protocol. Several recent studies involving plasmids encoding one or more viral proteins as an initial vaccine followed by a boost with inactivated virus [83] or purified protein [90] have demonstrated significant enhancement of immune responses. These results indicate that DNA priming followed by a boost with purified recombinant protein is a reasonable strategy to pursue in developing an effective vaccine against OvHV-2.…”
Section: Dna Vaccinesmentioning
confidence: 99%